2008
DOI: 10.1016/j.cell.2008.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Rad6-Rad18 Mediates a Eukaryotic SOS Response by Ubiquitinating the 9-1-1 Checkpoint Clamp

Abstract: Bacteria employ a coordinated SOS response to DNA damage by enhancing transcription, translesion synthesis, and recombination; a similar phenomenon has not been reported in eukaryotes. Here, we demonstrate that the ubiquitination complex Rad6-Rad18 is required for the increased transcription of a large number of yeast genes in response to DNA damage. Rad6-Rad18 promotes DNA-damage-dependent transcriptional induction as well as checkpoint functions by catalyzing monoubiquitination at the K197 residue of the Rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 64 publications
3
82
3
2
Order By: Relevance
“…Loss of the alternative clamp and clamp loader lowers the mutation frequencies in both organisms (104,207,229), and loss of the alternative clamp loader prevents Pol from being recruited to chromatin in S. pombe (104). Additionally, in a striking report, Fu et al have recently shown that the Rad6/Rad18 heterodimer monoubiquitinates the Rad17 subunit of the 9-1-1 complex to induce the DNA damage response in S. cerevisiae (54). Thus, the interplay of the two eukaryotic clamps in the recruitment of TLS polymerases and other factors is just beginning to be elucidated.…”
Section: Polymerase-switching Modelmentioning
confidence: 99%
“…Loss of the alternative clamp and clamp loader lowers the mutation frequencies in both organisms (104,207,229), and loss of the alternative clamp loader prevents Pol from being recruited to chromatin in S. pombe (104). Additionally, in a striking report, Fu et al have recently shown that the Rad6/Rad18 heterodimer monoubiquitinates the Rad17 subunit of the 9-1-1 complex to induce the DNA damage response in S. cerevisiae (54). Thus, the interplay of the two eukaryotic clamps in the recruitment of TLS polymerases and other factors is just beginning to be elucidated.…”
Section: Polymerase-switching Modelmentioning
confidence: 99%
“…71186-4REF; Novagen). Conditions for the quantitative real-time RT-PCR (qRT-PCR) and Western blot analyses were as previously described (19,20). The antibody used for Western blotting is the mouse anti-Myc monoclonal antibody 9E10 (Shanghai Genomics, China), diluted at 1:2,000.…”
Section: Methodsmentioning
confidence: 99%
“…Other DNA clamps have been described as well, which, as suggested by Langerak et al (2007), could be mobilized instead of PCNA. The 9-1-1 complex, which interacts in yeast with Polz (Sabbioneda et al 2005), has recently been shown to mediate an alternative DNA damage response after becoming similarly monoubiquitinated by the Rad6-Rad18 complex ( Fu et al 2008). The precise molecular requirements for the replicative bypass of abasic sites in mammalian B cells thus remain to be determined.…”
Section: Competitive Rather Than Alternative Repair Pathways In Hypermentioning
confidence: 99%